Research on the application of ceramic tableware design for young chinese consumers - Wenchao, Wu; Md Yusoff, Irwan Syah; Hj Alli, Hassan (Elite Scientific Publications, 2024)
This study investigates the demographic characteristics, consumption behavior, design preferences, and purchasing patterns of young Chinese consumers towards ceramic tableware. A sample primarily composed of 18-25-year-olds, predominantly female university students with undergraduate education and moderate income levels, was surveyed. Results indicate a strong preference for durable, aesthetically pleasing ceramic tableware, particularly within the price range of under 500 RMB. Consumption patterns reveal a focus on product quality and visual appeal, with online platforms being the preferred purchase channel, underscoring the pivotal role of e-commerce in the market. Design preferences lean towards warm tones and minimalist, practical styles, with a preference for traditional round shapes, especially in bowls. The study identifies significant market gaps, highlighting opportunities for innovation in diversified designs, improved craftsmanship, and multifunctional products. These insights are crucial for manufacturers and marketers aiming to tap into the growing demand among young Chinese consumers for culturally resonant yet modern ceramic tableware. © (2023), (Elite Scientific Publications). All Rights Reserved.